2016
DOI: 10.1038/srep28814
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-34 as a fibroblast-derived marker of liver fibrosis in patients with non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a common cause of chronic non-viral liver disease. Activation of macrophages and hepatic stellate cells is a critical step that promotes liver fibrosis. We aimed to explore the feasibility of interleukin-34 (IL-34), a key regulator of macrophages, as a fibrosis marker in patients with NAFLD. We enrolled 197 liver biopsy-proven NAFLD patients. We evaluated the serum levels of IL-34, macrophage-colony stimulating factor (M-CSF), soluble CD163 (sCD163), 40 cytokines/ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 43 publications
4
38
0
Order By: Relevance
“…12,13 Currently, the expression of IL-34 is identified as increase in patients with infection of various viruses, including HIV, 33 influenza A virus 34 and HCV. 35 15 Importantly, the increased IL-34 was associated with liver inflammation and fibrosis in HBV infection, and the results were consistent with the phenomenon observed in non-alcoholic fatty liver disease and chronic hepatitis C. 35,36 Besides these, IL-34 is shown to increase in different tumour cells, 26,[37][38][39] and related to the prognosis of various cancers. In addition, Zhou S et al showed that the upregulation of IL-34 contributed the development of HCC.…”
Section: Discussionsupporting
confidence: 77%
“…12,13 Currently, the expression of IL-34 is identified as increase in patients with infection of various viruses, including HIV, 33 influenza A virus 34 and HCV. 35 15 Importantly, the increased IL-34 was associated with liver inflammation and fibrosis in HBV infection, and the results were consistent with the phenomenon observed in non-alcoholic fatty liver disease and chronic hepatitis C. 35,36 Besides these, IL-34 is shown to increase in different tumour cells, 26,[37][38][39] and related to the prognosis of various cancers. In addition, Zhou S et al showed that the upregulation of IL-34 contributed the development of HCC.…”
Section: Discussionsupporting
confidence: 77%
“…Prothrombin activity and FIB‐4 index are markers for liver function and hepatic fibrosis, respectively. We previously reported an association between hepatic fibrosis and serum IL‐34 level in patients with NAFLD . In this study, the prevalence of Child–Pugh class B and C was high in the high IL‐34 group compared to the low IL‐34 group (data not shown).…”
Section: Discussionmentioning
confidence: 54%
“…We previously reported an association between hepatic fibrosis and serum IL-34 level in patients with NAFLD. 12 In this study, the prevalence of Child-Pugh class B and C was high in the high IL-34 group compared to the low IL-34 group (data not shown). Preisser et al reported that, in patients with HCV or HBV infection, injured hepatocytes secrete IL-34, which induces monocyte recruitment and differentiation into profibrogenic macrophages, as well as promoting type I collagen secretion by hepatic stellate cells.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…They demonstrated that the increase in MDSCs was only correlated with tumor progression, but not with hepatic fibrosis or the disease activity of chronic liver disease30. On the other hand, other research groups reported that M-CSF was associated with hepatic fibrosis in chronic hepatitis C and non-alcoholic fatty liver disease patients3132. Moreover, they found that M-CSF could be produced from hepatocytes with persistent HCV infection31.…”
Section: Discussionmentioning
confidence: 99%